Yarn mobility in woven fabrics – a computational and experimental study. (February 2016) - Tapie, E.; Guo, Y.B.; Shim, V.P.W.
Abstract : Establishment of a new experimental setup for out-of-plane yarn pull-out test. Effect of pre-tensioning the fabric regarding its resistance to yarn pull-out. Numerical model capable of simulating both in-plane and out-of-plane yarn pull-out. Greater sensitivity of fabric strain energy to fabric pre-tension than frictional dissipation. Effect of inversion of yarn natural profile on cyclic fluctuations of the pull-out force. Abstract: With the increasing usage of woven fabrics in various applications, an understanding of inter-yarn friction characteristics is useful for effective employment of such fabrics. Although the yarn pull-out test is a recognized method to ascertain yarn mobility within a weave, the physics governing yarn pull-out has not yet been fully examined, and previous finite element models were unable to reproduce the results of yarn pull-out tests. Consequently, fabric response involving yarn pull-out has not yet been well-understood in terms of the influence of inter-yarn friction and yarn crimp. The work undertaken provides insights into this by proposing a new yarn pull-out test procedure, which involves in-plane and out-of-plane pull-out; the latter is relevant to projectile penetration of fabric, during which yarns are often pulled out of the fabric plane. Pre-tension is also applied to fabric specimens, and its influence on the response is analyzed. The energy absorbed during out-of-plane pull-out is quantified, and yields insights into fabric performance. A finite element model is then developed to simulate yarn pull-out tests. To characterize inter-yarn friction, a Coulombic description that considers both static and kinetic friction, is implemented. The numerical model is able to describe both in-plane and out-of-plane yarn pull-out. The model is validated and used to identify mechanisms that restrain yarn mobility during yarn pull-out and how pre-tension affects this mobility. The local fluctuations in the experimental force-displacement curves are captured by the simulation, and are found to be caused by periodic alteration of the original crimped yarn profile during pull-out. Simulation results also show that most of the energy is dissipated by friction during yarn pull-out, and that the fabric stores strain energy. Pre-tension has a significant influence on both frictional energy dissipation, and strain energy in the fabric. Strain energy is found to be more sensitive to pre-tension than frictional dissipation, indicating that excessive restraint of yarn mobility may result in premature yarn failure.